Prevalence of and risk factors for hepatitis B and C viral co-infections in HIV infected children in Lagos, Nigeria - Lawal, Mary Adetola (PLoS One, 2020)
INTRODUCTION: The study was carried out to determine the prevalence of and risk factors for hepatitis B and C viral co-infections in HIV infected children in Lagos. METHOD: A cross-sectional study conducted to determine the prevalence and risk factors for hepatitis B and C viral co-infection in children aged 2 months to 13 years. There were 187 HIV infected and 187 HIV naïve age, sex-matched controls. Blood samples of participants were assayed for the serologic markers [HBsAg, anti-HBc, and anti-HCV)] of HBV and HCV viral infections using the Enzyme-Linked Immunosorbent assay (ELISA) method. RESULT: The prevalence of HBV infection using HBsAg was 5.3% and 4.8% (p = 0.814), among HIV-infected and HIV naïve children respectively, while using anti-HBc the prevalence was 7.0% and 7.5% (p = 0.842) among HIV- infected and HIV naïve children respectively. The prevalence of HCV infection among HIV- infected and HIV naive children were equal to 0.5% (p = 1.000). There was also no significant association with the identifiable risk factors (sharing of a toothbrush, sharing of needles, incision marks/tattoo, hepatitis B immunization status, history of blood transfusion, previous surgical operation, sexual exposure/abuse, history of jaundice, and genital circumcision) and the HBV and or HCV status among both groups of children. History of sexual exposure/abuse and history of jaundice were however found to be predictors of the presence of HBsAg among HIV infected children only, using a binary logistic regression model. CONCLUSION: The prevalence of HBV and or HCV infection among HIV-infected children is similar to the prevalence among HIV naïve children, suggesting that HIV-infected children are not more predisposed to viral hepatitis than healthy children. Also, there was no significant difference in the prevalence of HBV infection irrespective of the use of HBsAg or anti-HBc.